Prospects for Improving the Process of Considering Draft Laws in Parliament in the Context of the Updated Constitution (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the prospects for improving the lawmaking process in accordance with the updated Constitution. The new version of the Constitution creates the main legal and institutional foundations for the effective organization of lawmaking and the implementation of the state's legal policy. The article analyzes the legislative activity of the parliament and considers issues related to the tasks of its improvement. In particular, the main attention will be paid to the development of the sphere, the effective implementation of legal policy by studying new trends related to the digital transformation of the lawmaking process, as well as the expansion of the practice of adopting laws of direct action.